Social Media Addiction, Fear of Missing Out (FoMO) and Online Vulnerability in university students - Varchetta, Manuel (2020)
Despite the growing research on social networks sites (SNS), the associations between the abuse of these platforms, the phenomenon of Fear of Missing Out (FOMO) and Online Vulnerability has been understudied. The aim of this research was to provide a framework of attitudes and behaviors related to the use of the social network in young university students. In this study, the sample was composed to 306 Italian university students aged 18 to 30 (152 women; mean of age = 21.8; standard deviation = 3.19) who responded to an online survey regarding their SNS behaviors, Fear of Missing Out (FOMO), Basic Psychological Needs, Self-Esteem and Online Vulnerability. Correlations analysis showed a positive relationship between FOMO, Online Vulnerability, and Social Media Addiction. The results showed that women have a higher level of Social Media Addiction and the Need for Relatedness. The regression analysis showed that FOMO is the best predictor of Social Media Addiction. Implications of the findings in the educational field are discussed.